Multilingual Content, Digital Marketing, and Social Media Algorithms on Brand Loyalty through Brand Image of Local Skincare - Wibowo, M. Chandra; Ardiyanti, Silva; Dianthiny, Suci (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
The growth of digital technology and the high use of social media have changed consumer interaction patterns with brands, requiring the industry to optimize communication and marketing strategies to maintain customer loyalty. This research aims to analyze the influence of multilingual content, digital marketing, and social media algorithms on brand loyalty through brand image among Kahf skincare product users in Medan. The research used a quantitative approach with a causal design and involved 264 respondents selected using a purposive sampling method. Information was collected through a questionnaire and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The research results show that multilingual content, digital marketing, and social media algorithms have a positive and significant influence on brand loyalty and brand image. Brand image was also proven to have a positive and significant influence on brand loyalty, while also mediating the relationship between multilingual content, digital marketing, and social media algorithms and brand loyalty. Among all variables, social media algorithms had the greatest influence on brand image formation. These findings indicate that consumer loyalty is influenced not only by direct digital marketing activities but also by the industry’s ability to build a positive brand image through relevant, personalized, and consumer-preference-aligned communications. Therefore, strengthening brand image is a significant strategy for increasing consumer loyalty to the local skincare industry.